Analysis of the Effectiveness of Mediation by BPN in Land Dispute Resolution (Study in Klaten Regency) - Maharani, Mutiara (Semarang State University Undergraduate Law and Society Review, 2025)
Land is one of the natural resources that has a crucial role in supporting human survival. Human dependence on land is very high, both as residential land and as a source of livelihood. This article discusses the effectiveness of mediation conducted by the Klaten Regency National Land Agency (BPN) in resolving land disputes in the 2023-2024 period. This research uses an empirical juridical qualitative approach with primary data obtained through interviews with local BPN officials, as well as secondary data from legal literature and related regulations. The results show that the effectiveness of mediation conducted by the BPN is still low, with only 25% of cases successfully resolved. Factors causing mediation failure include the absence of the parties, egoism that inhibits compromise, and lack of legal understanding. The findings suggest that further efforts are needed to strengthen legal understanding, raise public awareness of the importance of peaceful resolution, and encourage active commitment from all parties involved in the dispute.